Keefektifan ekstrak daun sirsak, biji bengkuang, dan buah cabai jawa terhadap ulat grayak jagung (Spodoptera frugiperda (Smith)) (Lepidoptera: Noctuidae): Effectiveness of soursop leaves, yam bean seeds, and Javanese long pepper fruits extracts against larvae of fall armyworm (Spodoptera frugiperda (Smith)) (Lepidoptera: Noctuidae) - Agustini, Melia; Sartiami, Dewi; Dadang (Jurnal Entomologi Indonesia, 2024)
Fall armyworm (FAW), Spodoptera frugiperda (Smith) is an important pest on maize. Common control carried out by farmers in controlling the pest is by using synthetic insecticides. However, the improper use of synthetic insecticides can cause negative impacts. One strategy to control pests that is safe and environmentally friendly is by using botanical insecticides. Soursop (Annona muricata) leaves, yam bean (Pachyrizus erosus) seeds, and Javanese long pepper (Piper retrofractum) extracts are known to be able to control various insect pests. The aim of this research was to study the effectiveness of soursop leaves, yam bean seeds, and Javanese long pepper extracts on mortality of second instar larvae of FAW. Two test methods used to assess the three extracts on the mortality of S. frugiperda larvae were the leaf residual and the topical application methods. Insect mortality levels were processed using probit analysis to obtain lethal concentration (LC) and lethal dose (LD) values for each extract. The results showed that P. retrofractum extracts showed highest mortality effect on S. frugiperda than P. erosus and A. muricata extracts both on leaf residual and topical application methods. The LC50 and LC95 values of P. retrofractum extract were 0.142% and 0.595%, respectively. Meanwhile the LD50 and LD95 of P. retrofractum extract 0.10 µg/larvae and 0.40 µg/larva, respectively.